Palladium (II)-NNN Pincer Complex Embedded Carbon Felt Electrode for High-Performance Symmetrical Supercapacitor Applications - Gumrukcu, Selin; Kaplan, Ekrem; Arvas, Melih Besir; Kocyigit, Nilufer; Ozcesmeci, Mukaddes; Sahin, Yucel; Ozcesmeci, Ibrahim (WILEY-V C H VERLAG GMBH, 2025)
Pincer-type ligands are coated on the carbon felt (CF) surface in one step via the electrodeposition method, and their use as supercapacitor electrode materials is reported for the first time in this research study. Raman spectroscopy, X-ray diffraction, scanning electron microscopy-energy dispersive X-ray analysis and mapping, and X-ray photoelectron spectroscopy are used to characterize the bis(pyridyl) iminoisoindoline (BPI) derivates/CF electrodes. The galvanostatic charge-discharge study indicates that the calculated specific capacitance (Cs) of the PdBPI/CF electrode is 271.2 F g-1 at 1.0 mA current. The symmetrical supercapacitor has a high capacitance retention of up to 80.6% after 10 000 cycles, showing extended cycle life and strong electrochemical stability. The highest energy and power density values obtained for the PdBPI/CF symmetric supercapacitor are calculated to be 25.9 Wh kg-1 and 981.8 W kg-1, respectively.
Keywords: carbon felt electrodes; naphthol; palladium; pincer-ligands; supercapacitors; FLEXIBLE SUPERCAPACITOR; OXIDE NANOCOMPOSITE; PEROVSKITE OXIDES; FACILE SYNTHESIS; DOUBLE-LAYER; GRAPHENE; CELL; NANOSHEETS; OXIDATION; COMPOSITE; Energy & Fuels